If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -25 + -1(-15) = 0 Multiply -1 * -15 -25 + 15 = 0 Combine like terms: -25 + 15 = -10 -10 = 0 Solving -10 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3+y4=-y8 | | 10(12)=5(18) | | 47-6x=19+8x | | 7Z-3y=2 | | 6ax-4xb=12 | | N+(4.361)=59.78 | | -41=-3x-5 | | y=5.00+0.25x | | 9(x-1)+x=11 | | 6-9x=6x-9x-6 | | (x^2)+2x+40=(x^2)-x+190 | | 36r^2-1=0 | | 9y-8-6y+7=0 | | -25+55.5+(-29)= | | 6(-3x-3)=5x | | 7x+5x-54=72-6x | | 2c-58=7c-24 | | -15=5b+12-2b+b | | 3x+2+2x-1=6x-20 | | 35.8x+5.90=220.7 | | 17=6z-1 | | 36+(4x-9)=c(2x+1)+25 | | .666=3r | | 18x^2+18y^2-12x+9y+7=0 | | x^2-15x-15=-6x-5 | | -5+-16= | | 2b-8=0.4 | | (4x+7y)+(x-3y)= | | 5-2x=-5-x | | k+(4.21)=19.3 | | 13x+50=180 | | x^2-13x+28=-2x+4 |